Isolation of antibiotic resistance mutations in the rRNA by using an in vitro selection system - Cochella, Luisa (National Academy of Sciences, 2004)
Genetic, biochemical, and structural data support an essential role for the ribosomal RNA in all steps of the translation process. Although in vivo genetic selection techniques have been used to identify mutations in the rRNAs that result in various miscoding phenotypes and resistance to known ribosome-targeted antibiotics, these are limited because the resulting mutant ribosomes must be only marginally disabled if they are able to support growth of the cell. Furthermore, in vivo, it is not possible to control the environment in precise ways that might allow for the isolation of certain types of rRNA variants. To overcome these limitations, we have developed an in vitro selection system for the isolation of functionally competent ribosomal particles from populations containing variant rRNAs. Here, we describe this system and present an example of its application to the selection of antibiotic resistance mutations. From a pool of 4,096 23S rRNA variants, a double mutant (A2058U/A2062G) was isolated after iteration of the selection process. This mutant was highly resistant to clindamycin in in vitro translation reactions and yet was not viable in Escherichia coli. These data establish that this system has the potential to identify mutations in the rRNA not readily accessed by comparable in vivo systems, thus allowing for more exhaustive ribosomal genetic screens.